[RETRACTED] Effect of reaction temperature and inlet velocity of a bubble column reactor on the bubble size for biodiesel production - Mohd Yusof, Muhammad Nur Amirulhaq; Nasir, Nurul Fitriah (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Bubble column reactors (BCR) are multiphase reactors used in the production of biodiesel which can withstand a higher temperature and provide higher efficiency in the process. During the transesterification process in the bubble column reactor, the bubble will be produced and will affect the bubble column reactor performance in biodiesel production. Hence, the effect of various reactions of temperature and inlet velocity in a bubble column reactor on the sizes of the bubble for the transesterification reaction in the production of biodiesel is being determined in this study. For BCR models, two types of geometric models of the bubble column reactor with two different types of the perforated plate were designed by using SOLIDWORK 2018 and the analysis of simulation will evaluate by using CFD software which Ansys FLUENT with temperature used are 523K, 543K and 563K and the inlet velocity is 2 m/s, 4 m/s and 6 m/s. The main findings on effects on bubble sizes in the simulation based on the different values of the gas holdup obtained from the volume fraction of methanol vapor in volume mixture at various temperatures and inlet velocity. The results show that the temperature, inlet velocity and gas holdup affected the bubble sizes in the BCR as the results were validated with the simulated results of previous researches.